Gereja sebagai Tubuh Kristus : Menelusuri Sejarah, Makna dan Panggilan Kita dalam 1 Korintus 12:12-13 - Andeas Laoli; Malik Bambangan (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This essay explores the idea that the church is the body of Christ, as stated in 1 Corinthians 12:12-13. Studying the church history, theological meaning, and calling contained in this text helps us understand how the various members of the church function as one body under the leadership of Christ as the Head. These different roles demonstrate the strong connection between our faith in Christ and the work of the Holy Spirit uniting believers into one living body. In addition, this essay discusses how the calling of the church provides love, service, and spiritual growth that is in line with God's will.